(untitled) (CIPEEX, 2022)
THE PRESENCE OF ANY DENTAL CHANGES HAVE A NEGATIVE PSYCHOLOGICAL IMPACT FOR INDIVIDUALS, DUE TO THE EFFECT ON THE AESTHETIC APPEARANCE OF THE SMILE. IN THE EXTREMELY COMPETITIVE SOCIETY IN WHICH WE LIVE, AESTHETICS AND HARMONY DENTAL EXERT GREAT IMPORTANCE IN THE ACCEPTANCE AND SELF-ESTEEM. IN THE CURRENT SCENARIO, THERE IS A GROWING TENDENCY TOWARDS APPRECIATION OF AN AESTHETICALLY PLEASING SMILE, WHICH ENCOURAGES THE SEARCH FOR ALTERNATIVE TREATMENT TO MODIFY OR IMPROVE THE APPEARANCE OF THE SMILE. THE SEARCH FOR THE PERFECT SMILE ACCELERATED THE DEVELOPMENT OF THE DENTAL INDUSTRY IN TECHNOLOGY FOR THE IMPROVEMENT OF RESTORATIVE MATERIALS, IN ORDER TO REPRODUCE AS FAITHFULLY AS POSSIBLE THE DENTAL STRUCTURE, GETTING MORE AND MORE DESIRED AESTHETICS, WHICH IS SEEN AS FUNDAMENTAL IN MAINTAINING PHYSICAL AND MENTAL HEALTH OF THE INDIVIDUAL, A SIGN OF WELL-BEING AND PERSONAL AND PROFESSIONAL SUCCESS.IN MODERN DENTISTRY, COSMETIC PROCEDURES HAVE PROVIDING GREAR IMPROVEMENTS IN THE QUALYTY OF LIFE OF THE PEOPLE, WHOOFTEN ARE TRAPPED IN THEIR OWN DISHARMONY. THE DIRECT COMPOSITE RESIN ADHESIVE TECHNIQUE HAS ALLOWED NA EXPANSION IN THE OPTIONS OF AESTHETIC TREATMENTS TO ENHANCE THE NATURAL APPEARANCE OF THE TEETH SIMPLE, FAST ECONOMICAL AND CONSERVATIVE; RESTORING NOT ONLY THE HARMONY, BUT THE FUNCTION AND SELF - ESTEEM, MAKING THE INDIVIDUAL FEEL AGAIN INCLUED IN SOCIAL GROUPS AND IN THE SOCIETY IN WHICH HE LIVES. TOGETHEER WITH MINIMALLY INVASIVE PREPARATION TECHNIQUES, THE BONDED RESTORATIONS ALLOW THE RESOLUTION OF SITUATIONS OF AESTHETIC AND FUNCTIONAL DEFICIENCIES. THE PRESENTE WORK HAD AS OBJECTIVE TO EXPOSE, THROUGH PHOTOGRAPHIC PANEL, VARIOUS CLINICAL SITUATIONS OF AESTHETIC DISHARMONY, WHEN COMPOSITE RESIN WAS USED FOR THE SAKE OF AESTHETICS AND HARMONY, CONTRIBUTING GREATLY TO THE WELL-BEING AND SELF-WORTH OF THE INDIVIDUAL. KEYWORDS SELF-CONCEPT. QUALITY OF LIFE. ESTHETICS, DENTAL. COMPOSITE RESINS.